Chemical Composition Oil and Ethanol Extract of Nutmeg Leaf and Antibacterial Test Against Staphylococcus aureus and Pseudomonas aeruginosa - Kapelle, Imanuel Berly Delvis; Souhoka, Fensia Analda; Walla, Ainun Maharani (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
This study aims to determine the yield and composition of the essential oil and ethanol extract of nutmeg leaves and determine its antibacterial activity against Staphylococcus aureus and Pseudomonas aeruginosa bacteria. Nutmeg leaf oil was obtained by isolation using steam-water distillation and extraction methods using maceration with ethanol as solvent. The moisture content of nutmeg leaves is 11.11%. From the distillation method, 0.26% nutmeg oil was obtained, while the yield of nutmeg oil was 29.01% from the extraction method. Gas Chromatography-Mass Spectrometer analysis showed that distilled nutmeg oil contains 20 components with the main composition, namely myristicin (15.92%), b-phellandrene (14.35%), limonene (11.20%), b-pinene (10.81%), and a-pinene (8.59%). The ethanol extract of nutmeg leaf contains 37 components with the main composition being myristicin (7.64%), 1,1,3,3,5,5,7,7,9,9,11,11,13,13-tetradecamethylheptasiloxane (7.14%), 2,2-dimethyl-1-decanol (7.12%), bis(2-ethylhexyl) phthalate (5.55%), and 9-dodecane-1-al (4.63%). The antibacterial activity test of nutmeg oil was carried out using the good diffusion method. The inhibitory power of nutmeg oil and ethanol extract of nutmeg leaves against S. aureus bacteria were 20.31 mm and 23.56 mm, while against P. aeruginosa bacteria were 11.79 mm and 8.86 mm, respectively.